The teaching of digital journalism from a competency-based approach - Rodríguez Bazán, Grettel; Hernández Villa, Anniel; Campos Maura, Eraida (Transformación, 2024)
Objective: The article aims at systematizing the theoretical foundations of hypermedia journalism and assessing the potentials of competency-based education in that field.Methods: Theoretical level methods are used to allow the theoretical systematization and the logical analysis of the concepts.Result: The current dynamics of communication technologies and their influence on journalism leads to the evaluation of the curriculum and the inclusion of subjects intended to competency for hypermedia journalism development. The constant evolution of these subjects and contents demand problem solving and self-management of contents for the effective performance in the labor environment.Conclusion: Competency-based education generates a change in teaching-learning process planning focusing on individual needs and the inclusion of intra and transdisciplinary contents that generate a comprehensive approach to journalist education at the university.
Keywords: Competency-based education; journalism; Internet; professional education